2010
DOI: 10.1149/1.3484092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of La[sub 2]Zr[sub 2]O[sub 7] on Interfacial Resistance in Solid Oxide Fuel Cells

Abstract: The impact of La 2 Zr 2 O 7 ͑LZO͒ on interfacial resistance ͑R p ͒ at the La 0.78 Sr 0.20 MnO 3−␦ /yttria-stabilized zirconia interface was studied upon isothermal sintering at 1200°C for 2-25 h. Quantification of triple phase boundary length was performed by applying focused ion beam/scanning electron microscopy ͑FIB/SEM͒ serial-sectioning techniques and classical stereology. Electrochemical impedance spectroscopy was used to characterize the R p . The effect of LZO formation on microstructural models for R p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
1
23
0
1
Order By: Relevance
“…(25) The presence of La 2 Zr 2 O 7 at the electrode/electrolyte interface can be reasonably excluded because of the GDC layer between the electrode and electrolyte. (9,27) Changes in surface chemistry may affect the charge transfer reaction at the triple boundary region, causing degradation of ORR activity. Observed higher stability at elevated temperatures of A-site deficient LSM films demonstrates the correlation between the chemical stability and the electrode reactivity at elevated temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…(25) The presence of La 2 Zr 2 O 7 at the electrode/electrolyte interface can be reasonably excluded because of the GDC layer between the electrode and electrolyte. (9,27) Changes in surface chemistry may affect the charge transfer reaction at the triple boundary region, causing degradation of ORR activity. Observed higher stability at elevated temperatures of A-site deficient LSM films demonstrates the correlation between the chemical stability and the electrode reactivity at elevated temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Two sets of literature data reported by Mitterdorfer and Gauckler [34] and Chen et al [35] are used to scale kMCS and kT/J with the realistic sintering time and temperature, as well as to validate the kMC model. These two studies both experimentally investigated the sintering kinetics and the variation of TPB length for porous LSM electrodes on YSZ electrolytes under different conditions.…”
Section: Model Validationmentioning
confidence: 99%
“…For example, after 4 h sintering at 1200 C, a thinly layered La 2 Zr 2 O 7 is formed with a thickness of w45 nm. The thickness is increased to w75 nm after 20 h sintering [35]. Since the resolution of the present kMC model is 50 nm, which is insufficient to accurately capture this phenomenon, the reaction between LSM and YSZ is not i n t e r n a t i o n a l j o u r n a l o f h y d r o g e n e n e r g y 3 7 ( 2 0 1 2 ) 3 3 9 2 e3 4 0 2 considered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7) Extensive studies have shown that the cell performance degradation is caused by oxide segregation, 8),9) chromium deposition, 10) material deterioration, 11) and La 2 Zr 2 O 7 formation at LSM/YSZ interface. 12), 13) We have recently reported the stability of LSM cathode in humidified air 14) and carbon dioxide containing air. 15) In humidified air, SrO segregation on LSM cathode was enhanced by water content, electric bias, and low oxygen partial pressure; 14) in CO 2 -containing air, SrO converts to SrCO 3 at the LSM surface, resulting in initial performance degradation.…”
Section: Introductionmentioning
confidence: 99%